2017
DOI: 10.1017/s0033291717002392
|View full text |Cite
|
Sign up to set email alerts
|

Grey matter volume and thickness abnormalities in young people with a history of childhood abuse

Abstract: Childhood abuse is associated with widespread structural abnormalities in OFC-insular, cerebellar, occipital, parietal and temporal regions, which likely underlie the abnormal affective, motivational and cognitive functions typically observed in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 103 publications
2
70
0
1
Order By: Relevance
“…Over the last five years, review articles summarizing the neurobiological associations with childhood maltreatment have emphasized the long-lasting neurobiological structural and functional changes in the brain following maltreatment [21,83,183,184]. In brief, while null and conflicting findings are reported, data is converging to suggest childhood maltreatment is associated with lower gray matter volumes and thickness in the ventral and dorsal prefrontal cortex, including the orbitofrontal and anterior cingulate cortices, hippocampus, insula, and striatum, with more recent studies also suggesting an association with decreased white matter structural integrity within, and between, these regions [185][186][187][188][189][190][191][192][193][194]. Smaller hippocampal and prefrontal cortical volumes following childhood maltreatment are consistently reported in unipolar depression and other psychiatric disorders [189,[195][196][197][198][199], with gene by environment interactions suggested [200][201][202].…”
Section: Childhood Maltreatment and Associated Alterations In Neural mentioning
confidence: 99%
“…Over the last five years, review articles summarizing the neurobiological associations with childhood maltreatment have emphasized the long-lasting neurobiological structural and functional changes in the brain following maltreatment [21,83,183,184]. In brief, while null and conflicting findings are reported, data is converging to suggest childhood maltreatment is associated with lower gray matter volumes and thickness in the ventral and dorsal prefrontal cortex, including the orbitofrontal and anterior cingulate cortices, hippocampus, insula, and striatum, with more recent studies also suggesting an association with decreased white matter structural integrity within, and between, these regions [185][186][187][188][189][190][191][192][193][194]. Smaller hippocampal and prefrontal cortical volumes following childhood maltreatment are consistently reported in unipolar depression and other psychiatric disorders [189,[195][196][197][198][199], with gene by environment interactions suggested [200][201][202].…”
Section: Childhood Maltreatment and Associated Alterations In Neural mentioning
confidence: 99%
“…Indeed, the theoretical conceptualization of stress as falling along at least two dimensions—deprivation (i.e., absence of cognitive and socioemotional input) and threat (i.e., presence of physically harming input)—is increasingly being highlighted in the field ( McLaughlin et al, 2017 ; Nemeroff, 2016 ; Sheridan and McLaughlin, 2014 ). Empirical studies have shown that whereas experiences characterized by deprivation tend to be associated with reductions in cortical thickness in association cortex and in regions of the PFC ( Hanson et al, 2011 , 2012 ; McLaughlin et al, 2013 , 2017 ), experiences characterized by threat appear to affect the morphology and connectivity of regions involved in emotional learning, including hippocampus, amygdala, PFC ( Lim et al, 2017 ; Teicher et al, 2016 ), as well as the functional connectivity of regions in the CEN ( Hart et al, 2017 ). Studies by Teicher and colleagues have suggested further that different types of threatening experiences yield different neurobiological effects; specifically, whereas individuals exposed to parental verbal abuse exhibit morphological changes in structures responsible for processing auditory and linguistic stimuli, individuals who witnessed domestic violence exhibit morphological changes in structures responsible for processing higher-order visual information ( Teicher et al, 2016 ).…”
Section: Other Considerations For Future Research and Recommended Dirmentioning
confidence: 99%
“…A nuanced understanding of how early experiences alter structural brain development is critical to elucidating the mechanisms by which childhood adversity confers risk for psychopathology, and protective environmental factors buffer that risk. Early adverse experiences have been shown to disrupt neurodevelopment on a cellular level (Abbink et al, 2019;Bath et al, 2016;Bordner et al, 2011;Johnson & Kaffman, 2018), and a growing literature has identified alterations in structural brain features such as gray matter volume (De Bellis et al, 1999;Hair et al, 2015;Hanson et al, 2012;Hodel et al, 2015;Kribakaran et al, 2020;Mackes et al, 2020;McEwen, 2016;Noble et al, 2015;Sheridan et al, 2012;Teicher et al, 2016;Tottenham et al, 2010), cortical thickness (Gold et al, 2016;Kelly et al, 2013;Lim et al, 2018;McLaughlin et al, 2014;Monninger et al, 2019), white matter tract integrity (Bick et al, 2015;Hanson et al, 2013;Ho et al, 2017;Howell et al, 2013;Kircanski et al, 2019), and myelination (Bath et al, 2016;Bordner et al, 2011;Juraska & Kopcik, 1988;Makinodan et al, 2012) following adversity.…”
Section: Introductionmentioning
confidence: 99%
“…Examining findings across studies of specific types of adversity has also suggested unique associations with brain structure. For example, distinct regional patterns of reduced cortical thickness have been observed among children exposed to severe neglect in institutional care (Hodel et al, 2015;McLaughlin et al, 2014) versus children exposed to abuse (Busso et al, 2017;Gold et al, 2016;Lim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%